Physiological quality of Ingá seeds and seedlings stored and planted in different environments - Barrozo, Leandra Matos; Silva, Paloma Carneiro da; Santos, Joel Cabral dos [UNESP]; Lopes, Laísa Coelho dos Santos; Lima, Renato Pereira; Gomes, Josilda Junqueira Ayres (Centro Universitario de Maringa, 2022)
Inga ingoides (Rich.) Willd.) is a fruit tree used as food, reforesting and recovery of degraded areas. However, seeds of the genus Inga are recalcitrant and difficult to store. The physiological quality of seeds of I. ingoides stored in a fridge (5.0 ± 2°C) and ice chamber at 0.0 ± 2 and 15.0 ± 2°C during 28 days and the initial quality of seedlings for germination in a greenhouse and laboratory were evaluated. Assay was conducted in the Laboratory of Seed Analysis of the Department of Phytotechnicity and Phytohealth of the Universidade Estadual do Maranhão in São Luís MA Brazil. Fruits were harvested in São Luis, manually processed in the laboratory and retrieved for the germination and emergence (blank). Other seeds were conditioned in gerbox boxes and stored in a fridge (5°C and 47% relative humidity - RH); ice chamber (0.0°C and 49% RH) and ice chamber (15.0°C and 55% RH). Four tests were undertaken: water rate, germination, emergence, index of germination and emergence speed, length of seedlings at germination and emergence and dry weight of seedlings at germination and emergence. Storing of ingá seeds is feasible for two weeks in fridge without any loss of their physiological quality and placed to germinate in greenhouse.
Qualidade fisiológica de sementes e Plântulas de Ingá armazenadas e semeadas em diferentes ambientes
Keywords: Dissection; Inga ingoides; Propagation; Recalcitrant; Viability